Zinc electrodeposition from a chloride-free non-aqueous solution based on ethylene glycol and acetate salts. (10th February 2019) - Panzeri, G.; Muller, D.; Accogli, A.; Gibertini, E.; Mauri, E.; Rossi, F.; Nobili, L.; Magagnin, L.
Abstract: In this work, the electrodeposition of zinc is carried out from a chlorides-free organic solution based on ethylene glycol (EG) and acetate precursor salts. The formation of an EG-complex with zinc was observed through 1 H NMR. The electrochemical characterization was performed by means of cyclic voltammetry (CV) and linear sweep voltammetry (LSV) on platinum and steel respectively. Electrodeposition was investigated with both potentiostatic (from −1 V vs Pt to −2 V vs Pt) and galvanostatic (from −2 mA/cm 2 to −16 mA/cm 2 ) approaches together with Hull cell test: cathodic efficiencies > 85% were reported. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses showed that the films were compact, with large grains and a hexagonal microstructure preferentially oriented along the [002]/[102] directions. The high purity of the deposits was assessed by electron dispersive spectroscopy (EDS). Polarization tests in de-aerated 5 %wt NaCl solution resulted in a corrosion potential of Ecorr = −1.03 V vs Ag/AgCl (Icorr = 1.01 × 10 −6 A/cm 2 ).